PENGEMBANGAN FLIPBOOK BERBASIS QR CODE JENIS-JENIS TUMBUHAN PAKU (Pteridophyta) UNTUK MASYARAKAT KAWASAN GOA BATU - Sinta Bella Lestari; Merti Triyanti; Fitria Lestari (Jurnal Perspektif Pendidikan, 2023)
This study aims to find out the types of fern growth in the Batu Caves area and to develop a qr code based flipbook. Based on the results of research and data analysis, it was found that the developed QR Code-based Flipbook was suitable for use by the people of the Batu Caves area. In addition, it was concluded that the results of exploration of ferns (Pteridophyta) in the Batu Caves area of Taba Jemekeh Village found 22 species consisting of 12 families and 13 genera of ferns. Fern plants (Pteridophyta) which are commonly found in the Batu Caves area of Taba Jemekeh Village are the Dryopteridaceae family